Analisis Transparansi Dan Akuntabilitas Pengelolaan Keuangan Upacara Ngaben Keluarga“Nyama Sanggah” Pekarangan Arya Nyuh Aya Di Desa Kusamba, Kecamatan Dawan, Kelungkung Bali - Made Sandi Merta; Nyoman Trisna Herawati (Jurnal Ilmiah Akuntansi dan Humanika, 2022)
This research was conducted to find out (1) the background of Pekarangan Arya Nyuh Aye's choosing the "nyama sanggah" family’s ngaben, and (2) the accountability applied in maintaining transparency and accountability in financial management of the "Nyama sanggah" family’s ngaben. The method used is qualitative by using primary data and secondary data obtained through interviews, and documentation, which is then analyzed by data reduction, data presentation, and drawing conclusions. The results of this study are (1) rationale of the Pekarangan Arya Nyuh Aye choosing the "nyama sanggah" family’s ngaben, namely: (a) Efforts to accelerate the ngaben to avoid their ancestors becoming bhutacuil; (b) the existence of a principal, providing benefits of time relief for the bereaved family; (c) To elevate the existence of the Arya Nyuh Aya family in Pasurungan to the dadia level by building a sense of solidarity and the culture of metulungan. (2) The accountability that is applied is very simple, namely from a financial record book that is shown and delivered orally to all of Krama Arya Nyuh Aya.